Demarcating the rainfed unproductive zones in the African Sahel and Great Green Wall regions. (9th November 2020) - Elagib, Nadir Ahmed; Khalifa, Muhammad; Babker, Zryab; Musa, Ammar Ahmed; Fink, Andreas H.
Abstract: Farming and afforestation in the African Sahel and Great Green Wall (GGW) regions are constrained by climate variability, water scarcity, and degradation of lands. Yet, the debate on dynamics of the Saharan boundary and vegetation productivity in these regions is ongoing. Here, we trace the most unsuitable areas for rainfed agriculture and greening in the two regions over the period 1998–2017 without specifying a crop/vegetation type. A method is devised based on combining June–October rainfall/potential evapotranspiration (aridity index) and integrated normalized difference vegetation index (productivity index). The feasibility of the currently planned GGW is placed in the context of naturally‐sound afforestation. The results show certain features of the suitable zone for planting. A seasonal aridity index of 0.1 is a minimum threshold for vegetation vigour to begin. Given the strong interannual north–south progression and retreat of this seasonal level, the northernmost aridity isoline that dictates feasibility of rainfed productivity is found to correspond to the borderline between the arid and semiarid zones. This borderline is delimited by an average aridity index of 0.2. Accordingly, 1, 337, 535 km 2 (43.5%) and 729, 576 km 2 (25.6%) of the Sahel and the proposed GGW region, respectively, are not feasible for sustainable planting, that is, under rainfed and natural land fertility conditions. About 93.0% of the impractical GGW area lies east of longitude 10°E. Investing in a green belt east of this longitude is risky without supplementary irrigation. The contrasting productivity behavior across the GGW cautions the progression in this project without rigorous feasibility investigation.